A cohort study of gill infections, gill pathology and gill-related mortality in sea-farmed Atlantic salmon (Salmo salar L.) A descriptive analysis - Østevik, Liv (Journal of fish diseases, 2022)
© 2022 The Authors. Journal of Fish Diseases published by John Wiley & Sons Ltd.